10 - Les extrémismes développementalistes et leurs conséquences sur les pratiques de développement en Afrique subsaharienne - Amougou, Thierry (Africa Development, 2021)
Development studies invented themselves as a concept different of the object that they are studying by selecting facts and interpreting them. Thus, Max Weber created what he called « types idéaux » in the sense of a table of thinking which the target is to simplify and to rationalise the reality. This paper shows that the development process in sub-Saharan Africa has passed trough four determinist « types idéaux » mutually exclusive and presenting their prescriptions as the only road to follow in order to achieve development. This situation entails on the one hand rational territories, rational development practices, and rational actors to promote and, on the other hand, irrational territories, irrational actors and irrational development practices to struggle because they are out of the dominant model of the moment. Introducing contradictory dynamics seems to be able to overcome t is kind of classification between actors, territories and development practices.